«On the Road: individual, Society and the State in the Appropriation of Public Space - Afonso, Ana Isabel (2012)
The overall aim of this paper is to draw attention to a potential new domain of research - relevant within European national contexts – generally stated as ‘the impact of motorisation in society’ [by motorisation I mean the massive phenomena of automobile diffusion and its uses, as an important dimension that accompanied urbanization process in different world regions].